2016
DOI: 10.1007/s12035-016-0151-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Noncanonical Wnt Receptors Required for Wnt-3a-Induced Early Differentiation of Human Neural Stem Cells

Abstract: Wnt proteins preferentially activate either β-catenin-dependent or β-catenin-independent signals, but the activity of a particular Wnt also depends on cellular context and receptor availability. We previously reported that Wnt-3a induces neural differentiation of human embryonic stem cell-derived neural stem cells (NSCs) in a β-catenin-independent manner by activating a signal involving JNK and the AP-1 family member ATF-2. Here, we report the results of a gene silencing approach to identify the Wnt receptors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 47 publications
1
11
0
Order By: Relevance
“…Microarray analysis revealed upregulation of TBR2, DCX, and DLX2, among other genes, after Bangle extract and c -Banglene treatment. Previous studies have suggested that WNT/β-catenin signaling is involved in regulating the expression of TBR2, which is a marker of intermediate progenitor cells and is essential for neurogenesis [ 33 , 34 ], and DCX in NSCs of humans and mice [ 35 , 36 ], and it regulates DLX2 expression in the fetal mouse brain [ 37 , 38 ]. DLX2 expression in NSCs is known to be sufficient for differentiation into GABAergic neurons [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Microarray analysis revealed upregulation of TBR2, DCX, and DLX2, among other genes, after Bangle extract and c -Banglene treatment. Previous studies have suggested that WNT/β-catenin signaling is involved in regulating the expression of TBR2, which is a marker of intermediate progenitor cells and is essential for neurogenesis [ 33 , 34 ], and DCX in NSCs of humans and mice [ 35 , 36 ], and it regulates DLX2 expression in the fetal mouse brain [ 37 , 38 ]. DLX2 expression in NSCs is known to be sufficient for differentiation into GABAergic neurons [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is important to clarify whether Wnt5a‐Ror1 and Wnt5a‐Ror2 signaling affect division modes of NPCs in the developing neocortex. In human embryonic NPCs, Wnt3a, a representative canonical Wnt, can induce neural differentiation in a β‐catenin‐independent manner by activating JNK and ATF‐2 possibly through a receptor complex, comprising from Ror1, Fzd4/5, and LRP6 (Bengoa‐Vergniory et al, ).…”
Section: Functional Roles Of the Ror‐family Rtks In Npcsmentioning
confidence: 99%
“…ROR1 and the co-receptor LRP6 may heterodimerize in CLL cells as part of signal transduction [ 13 ]. KAN0439834 dissociated the ROR1/LRP6 complex (Supplementary Figures 4A and B ) and the complex proteins were dephosphorylated (Fig.…”
mentioning
confidence: 99%